Pengaruh Budaya Organisasi Dan Tanggung Jawab Kerja Terhadap Kinerja Karyawan Pada Pt Pos Indonesia Cabang Ciputat Di Tangerang Selatan - Lingga Manda Prakasa; Melda Wiguna (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to determine the effect of Organizational Culture and Work Responsibility on Employee Performance at PT. Pos Indonesia Ciputat Branch, both partially and simultaneously. This study uses an associative method with a quantitative approach. The population in this study amounted to 116 employees using the sampling technique using slovin sampling and obtained a sample of 90 respondents. This research uses SPSS version 26. Data analysis was carried out using simple and multiple linear regression, correlation coefficient, determination coefficient, t test, and F test. The results of the study indicate that Organizational Culture has a positive and significant effect on Employee Performance, as evidenced by the regression equation Y = 10.302 + 0.748 X1, with a correlation value of 0.973 (very strong) and a determination of 94.7%. The results of the t test show that t count is 8.972 greater than t table 1.987 with a significance of 0.000. Job Responsibility is also proven to have a positive and significant influence on Employee Performance, based on the regression equation Y = 9.305 + 0.765 X2, with a correlation value of 0.984 (very strong) and a determination of 96.9%. The t-test shows a calculated t of 8.438 > t table 1.987 with a significance of 0.000. Simultaneously, Organizational Culture and Job Responsibility have a significant influence on Employee Performance with a regression equation Y = 4.352 + 0.471 X1 + 0.431 X2, a correlation coefficient of 0.985 (very strong), a determination of 97.0%, and a calculated F value of 39.537 > F table 3.101 (significance of 0.000). It can be concluded that both variables have a significant influence on performance.